Antinuclear antibodies in non-systemic autoimmune rheumatic disease dermatological conditions - Mahayidin, Hasni; Bakrin, Ikmal Hisyam (Universiti Putra Malaysia, 2021)
Antinuclear antibodies (ANA) indirect immunofluorescence assay (IFA) is the first line immunological investigation, mainly for systemic autoimmune rheumatic disease (SARD). However, ANA is also being requested in certain dermatological conditions particularly in those with immune dysregulation as underlying pathogenesis. It is not uncommon to get positive ANA results in patients with non-SARD dermatological conditions. However, the clinical significance and usefulness of ANA has not been well established. This review summarises the available studies on ANA IFA in non-SARD dermatological conditions which include atopic dermatitis (AD), psoriasis, vitiligo and autoimmune bullous diseases. It aims to determine the prevalence of ANA, the commonly reported ANA titres and patterns, as well as any clinical associations between ANA and non-SARD dermatological conditions.